Natural Holobiome Engineering by Using Native Extreme Microbiome to Counteract the Climate Change Effects - Rodriguez, Rodrigo; Durán, Paola (Frontiers in Bioengineering and Biotechnology, 2020)
In the current scenario of climate change, the future of agriculture is uncertain. Climate change and climate-related disasters have a direct impact on biotic and abiotic factors that govern agroecosystems compromising the global food security. In the last decade, the advances in high throughput sequencing techniques have significantly improved our understanding about the composition, function and dynamics of plant microbiome. However, despite the microbiome have been proposed as a new platform for the next green revolution, our knowledge about the mechanisms that govern microbe-microbe and microbe-plant interactions are incipient. Currently, the adaptation of plants to environmental changes not only suggests that the plants can adapt or migrate, but also can interact with their surrounding microbial communities to alleviate different stresses by natural microbiome selection of specialized strains, phenomenon recently called "Cry for Help". From this way, plants have been co-evolved with their microbiota adapting to local environmental conditions to ensuring the survival of the entire holobiome to improve plant fitness. Thus, the strong selective pressure of native extreme microbiomes could represent a remarkable microbial niche of plant stress-amelioration to counteract the negative effect of climate change in food crops. Currently, the microbiome engineering has recently emerged as an alternative to modify and promote positive interactions between microorganisms and plants to improve plant fitness. In the present review, we discuss the possible use of extreme microbiome to alleviate different stresses in crop plants under the current scenario of climate change.